Effects of Golden Sea Cucumber Extract (Stichopus Hermanii) on Fasting Blood Glucose, Plasma Insulin, and MDA Level of Male Rats (Rattus Norvegicus) Induced with Streptozotocin - Prawitasari, Dita Sukmaya; Safitri, Indri; Notopuro, Harianto (Folia Medica Indonesiana, 2019)
Diabetes mellitus (DM) is one of disease that its incidence increases every year worldwide. The condition of DM can cause various complications caused by oxidative stress. Stichopus hermanii (SH) or golden sea cucumber extract contains antioxidant compounds that have been proven to reduce oxidative stress conditions. The purpose of this study was to investigate the effect of Stichopus hermanii extract on condition of diabetes mellitus by looking at changes in fasting blood glucose, plasma insulin, and malondialdehyde levels in animal models of Wistar rats. This study was a laboratory experimental study using Randomized Control Trial Design with Post-test only control group design. Thirty-five male Wistar rats divided into five groups, i.e normal control group, positive control, negative control and two treatment groups with SH extract dose 8.5 and 17 mg / kgBW for 14 days once daily after induction of Streptozotocin at the Biochemistry Laboratory of the Faculty of Medicine, Airlangga University. Fasting blood glucose level was measured by a glucometer, plasma insulin measured by ELISA and MDA level was measured by a spectrophotometer. Data were analyzed statistically by using One Way ANOVA test and Kruskal Wallis. There were significant results of SH extract can reduce fasting blood glucose (Kruskal Wallis, p=0.030) and MDA (Kruskal Wallis, p=0.042) but not in plasma insulin (ANOVA, p=0.130). The lowest MDA level occurs in the K4 group that given SH extract dose 17 mg/kg BW than another experimental group. As the conclusion, this study showed SH extract can decrease fasting blood glucose and oxidative stress in diabetic-induced rats.